The role of additional correction methods of insufficient adherence to treatment for effective blood pressure control in patients with resistant arterial hypertension - O. Voloshyna; V. Zbitnieva; S. Busel; A. Chaika; V. Samorukova; T. Dychko (Journal of Education, Health and Sport, 2016)
Voloshyna O., Zbitnieva V., Busel S., Chaika A., Samorukova V., Dychko T. The role of additional correction methods of insufficient adherence to treatment for effective blood pressure control in patients with resistant arterial hypertension. Journal of Education, Health and Sport. 2016;6(12):857-865. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.252818